Health Promotion on Environmental Waste Management At Elementary School In Bandung - Laillah Mukarrahmah; Ade Ajeng Rahmawati (Universitas Pendidikan Indonesia, 2023)
Background : Various activities in schools almost always produce waste. The waste generated from the school environment can be in the form of organic or inorganic waste. Accumulated waste can cause environmental pollution and can cause disease outbreaks. Garbage such as paper, leaves, or even leftover food from student supplies has not been managed properly by students. The garbage is still collected in the same trash can so that it can cause an unpleasant odor and interfere with the learning process. To reduce this, many approaches can be taken, such as more efficient waste management, recycling waste, and reducing waste use. Method: Health promotion activities are carried out using the extension method by providing material on good and correct waste segregation. The instrument used was a questionnaire to measure knowledge using frequency data distribution analysis. Result: Through this health promotion the level of students' knowledge about waste sorting has increased quite a bit. Conclusion: This health promotion can increase students' knowledge. It is hoped that this increase in knowledge will be followed by changes in the behavior of all school members. Schools should support this movement and facilitate the school community in sorting waste.